Electroactive performances of conductive polythiophene/hydrogel hybrid artificial muscle - Pattavarakorn,D. (Elsevier BV, 2015)
The conductive polythiophene/chitosan/carboxymethylchitosan (PTH/CS/CMCS) hydrogel were prepared in this study. Polythiophene was synthesized via oxidative polymerization in chloroform at 40°C. For CMCS synthesis, CS was alkalized with sodium hydroxide in isopropanol and then reacted with monochloroacetic acid at 50 °C. The synthesized PTh and CMCS were mixed with CS by solution blending, glutaraldehyde crosslink agent was added and then the conductive hydrogel films were casted. The effects of CS/CMCS ratio, glutaraldehyde concentration, electric field strength and PTh particle addition on conductive hydrogel properties; morphology, crystallinity, thermal stability, tensile strength and electroactive performances were investigated. The results show that the CS/CMCS hydrogel responses well to an applied DC electric field by bend towards electrode, in which the bending angle increases with the increase of electric field strength. The crosslinked CS/CMCS hydrogel shows better response than uncrosslinked hydrogel. Moreover, the conductive PTh/CS/CMCS hydrogel shows lower electroactive performances than the CS/CMCS due to its higher weight and rigidity. © 2013 The Authors.